The new developmentalism and productive sophistication - De Moraes, Isaías Albertin [UNESP] (2020)
The purpose of this article is to present the New Developmentalism school and its production about productive sophistication. The technical methodological procedures prioritized by the research, in this way, were bibliographical and documentary. The methodology is predominantly descriptive, so the research aimed at structuring and defining a theoretical model, mapping it. The article is divided into two sections. The first section presents the main precepts of New Developmentalism; the second section focuses on the production of the school about productive sophistication. In conclusion, the research sought to contextualize and to explain the described studies, exposing some hypotheses and questions.